2016
DOI: 10.1111/fcsr.12161
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges in Energy‐Related Boomtowns: Implications for Family and Consumer Science Professionals

Abstract: Economic prosperity in energy‐dependent regions has created unique opportunities and challenges for individuals, families, and communities. This study demonstrates how theory and research can guide family and consumer science (FCS) professionals in helping people adapt to disruptions caused by economic cycles. Evidence is derived from primary interviews with family business owners and others in the Bakken area of western North Dakota, and secondary data from the Uinta Basin area of Utah. The study provides gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Booms are often associated with positive effects for families and their communities: economic prosperity, tremendous employment opportunities within and outside the O&G industry, higher wages, and the ability of a single spouse to maintain an entire family economically. However, booms also have negative effects: heavy traffic and associated damage to infrastructure, environmental degradation, crime and safety concerns, youth dropping out of high school to work, and long working hours leading to less family time and more family conflict (Barnes et al., 2012; Ilies et al., 2007; Fitzgerald et al., 2016; O’Connor, 2015). Booms also attract a transient workforce that can contribute to overcrowding, conflicts between economic migrants and permanent residents because of cultural differences and limited job opportunities, as well as result in housing shortages and higher rents which are beyond the financial means of low‐income earners (Fitzgerald et al., 2016; O’Connor, 2015).…”
Section: Booms and Busts In Rural Resource‐cursed Extraction Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Booms are often associated with positive effects for families and their communities: economic prosperity, tremendous employment opportunities within and outside the O&G industry, higher wages, and the ability of a single spouse to maintain an entire family economically. However, booms also have negative effects: heavy traffic and associated damage to infrastructure, environmental degradation, crime and safety concerns, youth dropping out of high school to work, and long working hours leading to less family time and more family conflict (Barnes et al., 2012; Ilies et al., 2007; Fitzgerald et al., 2016; O’Connor, 2015). Booms also attract a transient workforce that can contribute to overcrowding, conflicts between economic migrants and permanent residents because of cultural differences and limited job opportunities, as well as result in housing shortages and higher rents which are beyond the financial means of low‐income earners (Fitzgerald et al., 2016; O’Connor, 2015).…”
Section: Booms and Busts In Rural Resource‐cursed Extraction Communitiesmentioning
confidence: 99%
“…Boom periods bring long work hours and above average salary and household income, while bust periods bring lower salaries or unemployment but a potentially better work–life balance for its employees (Ennis & Finlayson, 2015). Families and communities that are highly dependent on the well‐being of such industries are, therefore, faced with significant challenges at both ends of the business cycle (Barnes et al., 2016; Fitzgerald et al., 2016). Previous research has shown that families who live in rural communities that continuously rely on a single extraction industry face even more severe challenges than families who live in communities with more diversified economies (Shepard, Betz, & Snyder, 2019; Ungar, 2018).…”
Section: Booms and Busts In Rural Resource‐cursed Extraction Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially discovered in 1997, the practice combines more traditional methods of extraction with a horizontal drilling technique that involves fracturing shale with a “cocktail” of chemicals, sand, and water ( Rinaldi, 2015 ). Since 2008, a boom in fracking has brought temporary economic prosperity to rural communities at the same time that it has created significant environmental and human health concerns ( Fitzgerald et al, 2016 ; Murphy, 2020 ). While it is difficult to prove causal links between chemicals used in fracking and health problems, available research illustrates “significant associations” between emissions from fracking and negative health effects ( Wollin et al, 2020 ; see also; Mrdjen and Lee, 2016 ).…”
Section: Introductionmentioning
confidence: 99%